RELIEF EVOLUTION OF KANIV NEAR-DNIPER TERRITORY ON THE BASE OF BASE LEVEL AND VERTEX HYPSOMETRY SURFACES ANALYSIS - Tustanovska, L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Structural-morphometric analysis and study of Kaniv Near-Dniper relief with the using of the spatial analysis and modeling has been carried out. Base level and vertex hypsometry surfaces with different order have been created. There analysis allowed to define the phases of the relief evolution in this region. The geomorphological structure peculiarities of Kaniv mountains have been defined for each stage of there formation. The relief evolution character during neotectonic stage has been described.